Process intensification of esterification reaction for the production of propyl butyrate by pervaporation; Resource-Efficient Technologies; Vol. 3, iss. 1 : TECHNOSCAPE 2016: International Conference on Separation Technologies in Chemical, Biochemical, Petroleum and Environmental Engineering - Khudsange C. R. Chandrakant (2017, 2017)
Title screen